Possibilities and Challenges for Ionic Liquids in Hydrometallurgy - Romero-Figueroa, J; Quijada-Maldonado, E; Merlet-Venturelli, G; Cabezas-Cornejo, R; Olea-Chandia, F (Elsevier B.V., 2020)
Hydrometallurgy is an efficient way of recovering metal ions from mineral ores where the most important steps are the leaching of the minerals, the recovery and purification of metal ions by solvent extraction (SX), and the final electrowinning (EW) process. Ionic liquids (ILs) have been extensively applied in the above mentioned process technologies with the aim to make them environmentally friendly by replacing organic volatile solvents which generate large amounts of residues and losses by evaporation with ILs which can be reutilized due to their negligible vapor pressure. This article intends to present a comprehensive review about the most important factors that make ILs solvents better performers than organic solvents in these processes, including the environmental impact of ILs when they are incorrectly handled and the possible solutions in case of loss of solvents or spills. Finally, the challenges that ILs require to overcome before their use at an industrial scale are extensively discussed, considering the possibilities that these solvents have in applications like urban mining or hydrometallurgy of refractory minerals. © 2020 Elsevier B.V.